Usability of a prototype application for self-care of people with heart failure. - Sousa, Mailson Marques de; Lopes, Camila Takáo; Almeida, André Atanasio Maranhão; Silveira, Rayane Monteiro; Almeida, Taciana da Costa Farias; Gouveia, Bernadete de Lourdes André; Oliveira, Simone Helena dos Santos (Acta Paulista de Enfermagem, 2025)
Objective: To evaluate the usability of a mobile application prototype to promote self-care for people with heart failure. Methods: A descriptive, cross-sectional study was conducted with 16 people with heart failure undergoing outpatient follow-up. The Smartphone Usability QuestionnaiRE (iRE), with scores ranging from zero to 124 and classified from a usability level of 30 (totally or partially disagree) to 80 (totally agree), was used in the assessment of usability. Scores ≥ 70 points indicate good levels of usability. Data were analyzed using descriptive statistics. Results: Male participants corresponded to 62.5% of the sample; 62.5% were married/in a stable relationship, with complete elementary education; 75% had non-ischemic etiology and reduced left ventricular ejection fraction. The average score of the Smartphone Usability QuestionnaiRE was 109.75 ± 3.47, with a minimum of 102 and a maximum of 114 points. Usability was classified as level 80. All participants fully agreed on the clarity of information, language used in the texts, ease of use, usefulness of instructions provided and would recommend using the application. Conclusion: The application prototype showed good levels of usability, indicating that end users fully agreed on the technological innovation that met the recommendations for satisfaction, effectiveness and efficiency of use. Future studies will be conducted to evaluate its impact on self-care behavior and clinical health outcomes in people with heart failure.